2020
DOI: 10.13031/trans.13828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod on Growth, Digestive Enzyme Activity, Stress, and Oxidative Status of Juvenile Chinese Soft-Shelled Turtles (Pelodiscus sinensis) in a Greenhouse

Abstract: HIGHLIGHTSArtificial sunlight with the main components of UVB, UVA, and visible light was used to investigate the influence of photoperiod on large-scale farming of juvenile Chinese soft-shelled turtles in a greenhouse.The effects of photoperiod on digestive enzyme activity, stress, and oxidative status of juvenile Chinese soft-shelled turtles were revealed.The optimal photoperiod for juvenile Chinese soft-shelled turtles reared in a greenhouse was 0 h light:24 h dark.Abstract. To improve light conditions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Total darkness (0 L:24 D) has been reported to maximize LPS and AMS activities in the fairy shrimp (Branchinecta orientalis) [45,46], while a prolonged photoperiod (18 L:6 D) affects LPS and TRYP activities in spotted sea bass (Lateolabrax maculatus) [23]. Similarly, the highest TRYP and LPS activities in the Chinese soft-shell turtle were observed in complete darkness (0 L:24 D) [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total darkness (0 L:24 D) has been reported to maximize LPS and AMS activities in the fairy shrimp (Branchinecta orientalis) [45,46], while a prolonged photoperiod (18 L:6 D) affects LPS and TRYP activities in spotted sea bass (Lateolabrax maculatus) [23]. Similarly, the highest TRYP and LPS activities in the Chinese soft-shell turtle were observed in complete darkness (0 L:24 D) [30].…”
Section: Introductionmentioning
confidence: 99%
“…It exerts a profound influence on various physiological processes and feeding behaviors in aquatic animals [22], modulating growth performance and developmental stages [23][24][25]. Notably, light impacts the growth and development of diverse species, including fish [26,27], shrimp [28], crabs [29], other crustaceans [22], and turtles [30], along with various physiological responses. As a pivotal environmental element, light is instrumental in regulating the circadian rhythms of these organisms [31].…”
Section: Introductionmentioning
confidence: 99%
“…But, in some tropical fish species, the correlation has been reported to be negative, as in Clarias gariepinus , which shows increased growth in the complete night with short day length (Almazán‐Rueda et al, 2005 ; Mustapha et al, 2012 ), and in Labeo rohita where prolonged photoperiod negatively affected growth (Shahjahan et al, 2020 ). In some cases, no photoperiod effect has been identified, as in the catfish Lophiosilurus alexandri (Kitagawa et al, 2015 ) or the Chinese softshell turtle Pelodiscus sinensis (Li et al, 2020 ; Xianqing et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod is one of the most crucial signal factors that regulate the proper phasing of behavioral and physiological variables such as feeding, energy metabolism, and neuroendocrine functions [1]. Nowadays, in terms of light control for culture purposes or environmental problems, how animals will respond to extreme light cycles (herein meaning constant darkness or constant light) has received great attention [2][3][4], with the focus mostly on birds and rodents. The soft-shelled turtle Pelodiscus sinensis is a freshwater reptile with great economic value, living at the bottom of water with dim light with a preference to feed in the dark [5].…”
Section: Introductionmentioning
confidence: 99%
“…The soft-shelled turtle Pelodiscus sinensis is a freshwater reptile with great economic value, living at the bottom of water with dim light with a preference to feed in the dark [5]. It has been reported that 24 h of darkness is beneficial to the feeding and growth of the soft-shelled turtle [3,5]; however, the underlying physiological mechanism is not yet clear. Few studies have explored the effect of light on physiological processes in turtles.…”
Section: Introductionmentioning
confidence: 99%